The Number of the Beast in Revelation 13 in Light of Papyri, Graffiti, and Inscriptions - Koester, Craig R. (Journal of early Christian history, 2016)
Revelation’s portrayal of a tyrannical beast concludes with a riddle, which identifies the beast’s number as 666 (Rev. 13:18). Among the factors that complicate the interpretation of the riddle are: first, that there is a notable textual variant that reads 616 instead of 666; second, that there are differences over the appropriate method of interpretation; and third, that even those who agree about method may reach different conclusions. Many scholars find the most plausible interpretation to be that the number summarises the numerical value of ‘Nero Caesar’ written in Hebrew characters, while others find this proposal unconvincing. This article provides fresh support for the ‘Nero Caesar’ interpretation by examining recently published graffiti from the agora at Smyrna, papyri from Oxyrhynchus, Ketef Jericho, and Murabba‘at, and inscriptions from the synagogues at Sardis and Dura Europos.